HUBUNGAN RASA SYUKUR DAN PERILAKU PROSOSIAL TERHADAP PSYCHOLOGICAL WELL-BEING PADA REMAJA AKHIR ANGGOTA ISLAMIC MEDICAL ACTIVISTS FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Wicaksono, M. Lutfi Hadi; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana, 2016)
Psychological well-being is a construct associated with the optimum or positive functioning of a person. All of the people exactly want to live well both physically and psychologically including adolescents. One of the factors who has a significant correlation with psychological well-being is gratitude. Psychological well-being of adolescents can also enhanced through the development of positive behaviors. One of positive behavior that support the personal growth of adolescents is prosocial behavior. This study aimed to determine the correlation between gratitude and prosocial behavior toward psychological well-being in late adolescents who join the Islamic medical activists at Faculty of Medicine Udayana University. The sampling technique used in this study was cluster sampling. Subjects of the research were 60 late adolescents who join the Islamic medical activists at Faculty of Medicine Udayana University. Instruments in this study were psychological well-being scale, gratitude scale and prosocial behavior scale. Data obtained in this study were analyzed by multiple regression analysis to see the correlation between gratitude and prosocial behavior toward psychological well-being. Multiple regression analysis results F test values 29,976 with significance value 0,000 (P < 0,05) it means gratitude variable and prosocial behavior were able to predict psychological well-being. Coefficient of determination equal to 0,513 showed that 51,3% psychological well-being can be explained by gratitude and prosocial behavior. Keywords: gratitude, prosocial behavior, psychological well-being, late adolescents